The Nasserist model of development and its implications for the Egyptian economy. Possibilities and limits of the experience of economic modernization - Méndez, Salua Youssef (Papeles de Europa, 2019)
The Nasserist experience throughout the period 1952-1970 allowed alternative forms of economic development to those that existed to that time in the region. In addition, it traced the origins of Pan-Arabism seen as the expression of a desire for independent and national development that would break with the western and imperialist domination to which most of the Arab countries were subject during these years.Throughout this investigation, we approach the analysis of the Nasserist experience in terms of possibilities and limits as well as its specificities at the economic level. On the basis of the theoretical framework of the paradigm of modernization and by examining the main strategies implemented, we defend the existence of an Egyptian way of trying to overcome underdevelopment. Far from being a perfect model of development, its impact on the economy was positive but limited: it allowed a process of modernization of Egyptian society, but it did not achieve a structural change.
Keywords: Arab economies; Egypt; Nasser; modernization; structural change